SLANG LANGUAGE USE IN @NIKITAMIRZANIMAWARDI_172 INSTAGRAM ACCOUNT - Agus Darma Yoga Pratama (Faculty of Letters Universitas Balikpapan, 2024)
The dynamic development of language enables the emergence of new languages and meanings in society. The development of slang among adolescents is very creative and creates new slang. This study aimed to identify the function of slang used on Instagram @nikitamirzanimawardi_172. A qualitative method with a qualitative descriptive approach was used in this study to explain the function of slang. Slang on the Instagram account @nikitamirzanimawardi_172 as a data source. The data collection technique used was the technique of reading and noting. Based on the results of data analysis, this study showed that there are 9 functions of using slang on the Instagram account @nikitamirzanimawardi_172, including: as a joke or just for fun, to look different and up to date, avoid preamble, enrich vocabulary, for several purposes certain (refining and emphasizing rejection, and reducing the excessive seriousness of a conversation), to show group membership, to ease social relations, and to show solidity, reality. There were also types of slang, such as jargon, prokem, and colloquial. Based on the results of this study, it was hoped that it will become a source of information for further research, considering that language has developed over time. Keywords: slang language, function, Instagram